Effects of Allogenic Dermal Fibroblasts on Rotator Cuff Healing in a Rabbit Model of Chronic Tear. Issue 8 (July 2018) - Kwon, Jieun; Kim, Yun Hee; Rhee, Sung-Min; Kim, Tae In; Lee, Jimin; Jeon, Saewha; Oh, Joo Han
Background: The failure of rotator cuffs to heal after repair is an unresolved surgical issue. There have been substantial efforts, including the use of biological supplements, to enhance tendon healing. Dermal fibroblasts are a good candidate for tendon tissue engineering because they are similar to the tenocytes used for collagen synthesis. In addition, they are easily accessible because autologous dermal fibroblasts can be obtained from individual skin without major skin defects and allogenic dermal fibroblasts (ADFs) have already been commercialized in the field of skin engineering. Purpose: To determine the effects of dermal fibroblasts on tendon-to-bone healing in a rabbit model of a chronic rotator cuff tear. Study Design: Controlled laboratory study. Methods: A total of 33 rabbits were randomly allocated into 3 groups (n = 11 each). Supraspinatus tendons were detached and left for 6 weeks to establish a chronic rotator tear model. Torn tendons were repaired in a transosseous manner with the injection of 5 × 10 6 ADFs with fibrin in group A, fibrin only in group B, and saline only in group C. At 12 weeks after repair, the mechanical test and histological evaluation were performed. Results: Seven rabbits died before the evaluation (1 in group A, 2 in group B, 4 in group C). In the final evaluation, the mean ± SD load to failure was 48.1 ± 13.3 N/kg for group A, 34.5 ± 8.9 N/kg for group B, and 31.1 ± 8.3 N/kg for group C, and group A showed significantly higher load-to-failure values than the other groups ( P = .011). The midsubstance tear rate, which presented stronger tendon-to-bone healing than insertional tear, was 50.0% in group A, 22.2% in group B, 28.6% in group C, but the differences were not statistically significant ( P = .413). In the histological evaluation, group A showed greater collagen fiber continuity and better orientation than the other groups. Conclusion: This controlled laboratory study verified, on the basis of biomechanics and histology, the potential for the use of ADFs in rotator cuff healing. The current results suggest a new biological supplement to increase the rate of rotator cuff healing. Clinical Relevance: The most important finding of this study was the potential for a new biological supplement to enhance rotator cuff healing—a continuing challenge.